Immediate post-operative effects of different periodontal treatment modalities on oral health-related quality of life: a randomized clinical trial - Onur Ozcelik (Bohn Staflcu Van Loghun, 2007)
Aim: Oral health-related quality of life (OHQoL) characterizes a person’s perception of how oral health influences an individual’s life quality. The aim of this study is to investigate how the treatment modalities may affect the immediate post-operative quality of life of patients with periodontitis. Materials and Methods: Sixty psychologically and socio-demographically matched periodontitis patients were randomly divided into three groups [20 non-surgical (NS), 20 surgical (SG), 20 surgical plus enamel matrix protein derivative (S1EMD)]. The OHQoL was assessed with two patient-centred outcome measures [Oral Health Impact Profile-14 (OHIP-14) and General Oral Health Assessment Index (GOHAI)] in the post-operative period of 1 week. Results: Whereas there were no differences of OHQoL at the baseline, the patients treated by surgery had reported that they had experienced a worse OHQoL compared with the NS and S1EMD groups both in the OHIP-14 and GOHA indexes (p50.001). Conclusions: The results of this study clearly indicated that patient perceptions on the immediate post-operative period were significantly better in the NS and S1EMD groups when compared with the SG group. These findings need to be confirmed in further studies with larger populations.